Development of plant-friendly vermicompost using novel biotechnological methods - Kocaman, Ayhan; Turan, Metin; Tüfenkçi, Şefik; Katırcıoğlu, Hikmet; Güneş, Adem; Kıtır, Nurgül; Giray, Gülay; Gürkan, Burak; Ersoy, Nilda; Yıldırım, Ertan (Springer Science and Business Media LLC, 2023)
For the first time in the world, raw tea waste from tea plants was mineralized by rapid biotechnological methods using beneficial worms, enzymes (protease, lipase, dehydrogenase, hydrolase, urease, nitrogenase, cellulase) and microorganisms (Aspergillus flavus, Bifidobacterium spp. Bacillus subtilis, Rhodotorula spp., Lactobacillus, Rhodopseudomas spp.). Thus, biocompost technology was developed to create an exclusive organic tea fertilizer. The biocompost product was developed in a plant-friendly format for sustainable use of local resources. It was rich in organic material and free from diseases and pathogens, according to organic farming methods. It was also reliable in terms of heavy metal content. In the biocompost study, the application of five different compost mixtures and three different application methods were investigated. Worm + Plant Growth-Promoting Rhizobacteria + enzymes accelerated the mineralization of the compost among the studies, and the lowest C/N and OM % ratio was obtained. The other physical and chemical parameters were also in accordance with the ideal values determined in the literature. Also, the increase of nitrogen without nitrogen loss during the composting process shows that mineralization was successfully completed. In concluded, it can be suggested that the developed organic worm compost fertilizer can be used on agricultural land and in regenerative agriculture.
Keywords: 2. Zero hunger; 13. Climate action; 12. Responsible consumption